Enhancing cadmium and salinity stress tolerance in upland rice through priming: unraveling the impact of signaling molecules - Jéssica Batista Ribeiro e Oliveira; Heloisa Oliveira dos Santos; Anna Carolina Abreu Francisco e Silva; Antonio Rodrigues da Cunha Neto; Letícia de Aguila Moreno; Flávia Barbosa Silva Botelho (Journal of Seed Science)
ABSTRACT: Priming associated with signaling molecules is an effective technique to promote uniform and rapid germination in the field, in addition to increasing stress tolerance. This study aimed to evaluate the effect of priming solutions on tolerance to cadmium and salinity stress in two upland rice cultivars, Douradão and Soberana. Five priming agents were tested: indole acetic acid (IAA), melatonin, sodium nitroprusside (SNP), hydrogen peroxide (H2O2) and chitosan. After treatment, the seeds were subjected to three germination conditions: control (no stress), saline stress and cadmium stress. Evaluations included seed moisture content, germination percentage, seedling growth and activity of antioxidant enzymes (superoxide dismutase - SOD, catalase - CAT and ascorbate peroxidase - APX). The results showed that the effects of priming varied according to the type of stress and the agent used. Under saline stress, H2O2 favored germination and root growth, while under cadmium stress, IAA, melatonin and H2O2 were more effective. Chitosan induced high SOD activity in the cadmium stress, and SNP stood out for salinity. H2O2 increased APX activity in the cultivar Soberana, while SNP was more effective for Douradão in both stress conditions. Catalase was activated by H2O2 and melatonin. The study concludes that SNP, H2O2 and IAA can improve stress tolerance during rice seed germination by activating antioxidant systems that favor growth under adverse conditions.